Outcome predictors in patients (older than 14 years) with acute febrile encephalopathy: Role of cerebrospinal fluid analysis - Nandmer , Vijay Kumar; Nandmer, Ajay Kumar (Asian Journal of Medical Sciences, 2022)
Background: Managing patients with acute febrile encephalopathy (AFE), characterized by fever and altered mental status, is one of the primary reasons for hospitalization and mortality. Understating the predictors of AFE outcome will assist the physician in providing early clues and subsequent inventions to tackle the problem. Aims and objectives: To evaluate the predictors of outcome in patients with AFE, focusing on the cerebrospinal fluid (CSF) analysis. Materials and Methods: A prospective observational study was performed on 507 patients with fever and altered mentation (above 14 years of age) in the Department of General Medicine between December 2017 and May 2019. CSF analysis was done to obtain protein, glucose, cell count, and adenosine deaminase (ADA). Computed tomography/magnetic resonance imaging and PS for malaria parasites were also performed. Results: AFE was more common in males (54.63%). Tuberculous meningitis (TM) (44.8% vs. 41.6%) followed by bacterial meningitis (BM) (25.7% vs. 25%) was the most common diagnosis in females and males respectively. Mortality was more common in TM (57.4%) followed by BM (21.3%) patients. Of the 211 patients with TM, those who died had CSF protein ≥90 (49.7%; P= 0.012), CSF glucose ≥35 (53.2%; P=0.002), CSF cells ≥60 (47%; p=0.012) and ADA ≥15 (31.5%; P<0.001). Of the 127 patients with BM, those who died had CSF protein ≥90 (100%; P<0.001), CSF glucose ≥35 (78.3%; P <0.001) and CFS cells ≥60 (100%; P <0.001). Conclusion: CSF analysis could be important for predicting the outcome and should be done as soon as possible after the clinical judgment of the AFE.